Comparison of results of the manual and automated scoring of micronucleus frequencies in 60Co-irradiated peripheral blood lymphocytes for triage dosimetry. (March 2015) - Tamizh Selvan, G.; Chaudhury, N.K.; Venkatachalam, P.
Abstract: Scoring micronuclei in the peripheral blood lymphocytes of individuals exposed to ionizing radiation is a rapid biodosimetry assay. Peripheral blood lymphocytes from five individuals were exposed in vitro to 0–5 Gy of 60 Co γ-radiation at a dose rate of 0.76 Gy/min. The blood cultures were initiated with RPMI-1640 (80%) supplemented with FBS (20%), stimulated with mitogen and incubated at 37 °C for 44 h. At the 44th hour, cytochalasin-B (6 µg/mL) was added, and the cultures were incubated for 28 h more. The cells were harvested with a pre-chilled hypotonic solution (0.075 M) and fixed with a Carnoy's solution (methanol/acetic acid 5:1). Giemsa- and propidium-iodide-stained cells affixed to slides for microscopy were scored manually and automatically with the micronucleus scoring software from MetaSystems. The micronucleus frequencies determined in the Giemsa-stained cells by manual and automated scoring were 23.6% different ( P <0.0001) with an efficiency of 24.9%. Slides stained with propidium iodide are a better choice for automated scoring than Giemsa-stained ones. Highlights: Stains (Giemsa and PI) used did not influence the MN dose response. No significant variation in the MN yield at lower doses between scoring methods. Automated scoring of MN in PI stained cells would be the choice for triage.